2010
DOI: 10.1016/j.ijrobp.2009.02.059
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Concurrent Taxanes Enhance Both the Pulmonary Metabolic Radiation Response and the Radiation Pneumonitis Response in Patients With Esophagus Cancer

Abstract: Purpose The primary aim of this study was to quantitatively assess pulmonary radiation toxicity in patients who received thoracic radiotherapy combined with induction and/or concurrent chemotherapy with or without taxanes for esophageal cancer. Materials/Methods Subjects were 139 patients treated at The University of Texas M. D. Anderson Cancer Center for esophageal cancer and who had [18F]-fluorodeoxyglucose positron emission tomography/computed tomography imaging from November 1, 2003 to December 15, 2007,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
1
21
2
1
Order By: Relevance
“…While some studies have suggested that rates of esophagitis are higher with platinum agents than with taxanes (13, 14), data directly comparing chemotherapeutic agents and the risk of esophagitis in locally advanced NSCLC are sparse. Moreover, our institution recently reported an association between taxanes and an increased risk of pneumonitis (15). Given the prevalence of taxanes in definitive chemoradiation, the toxicity profile should continue to be explored both prospectively and retrospectively, particularly as radiation doses are further escalated.…”
Section: Discussionmentioning
confidence: 98%
“…While some studies have suggested that rates of esophagitis are higher with platinum agents than with taxanes (13, 14), data directly comparing chemotherapeutic agents and the risk of esophagitis in locally advanced NSCLC are sparse. Moreover, our institution recently reported an association between taxanes and an increased risk of pneumonitis (15). Given the prevalence of taxanes in definitive chemoradiation, the toxicity profile should continue to be explored both prospectively and retrospectively, particularly as radiation doses are further escalated.…”
Section: Discussionmentioning
confidence: 98%
“…35, 36 Finally, even though we found that the GTV was the most common site of initial failure, our patients also experienced high rates of systemic failure; thus efforts to increase local control may not necessarily translate into improved survival unless systemic therapies also improve. Thus far, trials to evaluate intensification of chemotherapy through the addition of induction chemotherapy have shown a mixed response 37, 38 . Perhaps the utility of this approach will not be fully realized until the high local failure rate is addressed.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs after radiotherapy for esophagus cancer 6, 7 and for breast cancer 8 . Radiation pneumonitis is an inflammatory reaction within irradiated normal lung tissue in response to radiation injury 9, 10 .…”
Section: Introductionmentioning
confidence: 99%